PRESENTATION AND MANAGEMENT OUTCOME OF ECLAMPSIA AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Sultana, Ruqqia; Bashir, Rubina; Khan, Bushra (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out evaluate to epidemiology, clinical presentation and prognostics aspects of patients presenting with eclampsia. Methods: This study was carried out at Gynae C unit of Ayub Teaching Hospital Abbottabad from 1st July 2003 to 31st October 2004. All patients presenting with eclampsia to the labor ward were included in the study. The diagnosis was based on history and confirmed on clinical findings of hypertension, oedema, proteinuria superimposed with fits. Patients with history of fits during pregnancy, labor and peurperium other than eclampsia were excluded from study. History physical findings and base line investigation were recorded on a proforma. Results: A total of 2100 admissions were made in the labor ward during this period and out of them 68 cases (3.23 %) were of eclampsia. Out of them 28 were primigravidae, 14 multigravidae and 26 grandmultigravidae. The seasonal frequency of cases was 29.41% in winters, 42.64% in autumn, 19.11% in summers and 8.82% in spring. Out of these 11.76% cases were complicated with retroplacental haemorrage and the same number with aspiration pneumonia, while Cerebrovascular Accident (2.94%) Acute tubular necrosis (2.94%) and Disseminated intravascular clotting (4.4%) were also seen. Among the new borns prematurity was found to be the major cause of perinatal mortality. Conclusion:Eclampsia is a dreadful complication of Pre Eclamptic Toxemia of pregnancy associated with high perinatal and maternal mortality. A qualitative and quantitative improvement in prenatal consultation should make it possible to reduce incidence of eclampsia measuring arterial blood pressure daily during antenatal period and for at least 14-days postpartum appears to be necessary for diagnosis and treatment for all cases of hypertension. Keywords: Eclampsia, PET, Pregnancy